On some parameters of Parity Signed Graphs - et. al., Reshma R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The parameters of parity signed graph mentioned in this paper are- rna and adhika number. The rna number of a parity signed graph S∗ is the minimum number of negative edges among all possible parity labelling of it’s underlying graph G, whereas adhika number is the maximum number of positive edges among all possible parity labelling of it’s underlying graph G.This paper mainly focuses on rna number and adhika number for certain classes of parity signed graphs..